design and documentation of a mechanical system for a residential building in hebron - Abo Markheyh, Hamza; Mraqtan, Khaled; Skakiya, Basil (جامعة بوليتكنك فلسطين - كلية الهندسة - ميكانيك, 2016)
This project aims to design mechanical systems that will serve the residential building which is located at al-haras street, hebron. The project is going to provide an integrating mechanical service to that building in regard to the air conditioning , fire fighting and plumbing systems. The building consists of four floors as well as a basement , each floor has an area of about 1300m2 on which seven apartments are constructed. The selected system for air conditioning in the building is variable refrigerant flow (VRF) type DVM plus 4 because of its high performance ( efficiency) and its environmental friendly. The selected systems for freighting are extinguishers , and fire hose cabinets. Also , jockey pump is used in order to rise the head.
no of pages 125, 29356, ميكانيك 5/2016 , in the store
Keywords: a mechanical systems